2016
DOI: 10.1111/modl.12340
|View full text |Cite
|
Sign up to set email alerts
|

The L2 Motivational Self System and L2 Achievement: A Study of Saudi EFL Learners

Abstract: The research reported in this article explores the relationship between Dörnyei's (2005, 2009) Second Language Motivational Self System (L2MSS) and the L2 proficiency level of Saudi learners of English as a foreign language (EFL). Male and female participants (N = 360) responded to a questionnaire relating to the main components of L2MSS, the ideal L2 self, the ought‐to L2 self, and the L2 learning experience, as well as learners’ intended learning efforts. The participants’ L2 proficiency was then measured wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
142
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(156 citation statements)
references
References 24 publications
9
142
5
Order By: Relevance
“…Motivation has been sought and techniques have been tried in Saudi Arabia with fruitful outcomes. Alshahrani (2016), Alshehri (2009), and Moskovsky et al (2016) investigated the validity of the motivational self-system in Saudi Arabian EFL context. Mahdi (2015) developed strategies to motivate reluctant students and Al-Zubairy (2012) studied integrative and instrumental motivation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Motivation has been sought and techniques have been tried in Saudi Arabia with fruitful outcomes. Alshahrani (2016), Alshehri (2009), and Moskovsky et al (2016) investigated the validity of the motivational self-system in Saudi Arabian EFL context. Mahdi (2015) developed strategies to motivate reluctant students and Al-Zubairy (2012) studied integrative and instrumental motivation.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In the few exceptions that did include a form of L2 achievement (e.g., Dörnyei & Chan, 2013;Eid, 2008;Kim & Kim, 2011;Lamb, 2012;MacIntyre & Serroul, 2015;Moskovsky et al, 2016), the results are not optimistic. In the two languages they examined, Dörnyei and Chan (2013) reported a relatively strong correlation between the Mandarin ideal L2 self and grades in Mandarin (r = .42), but a weaker correlation between the English ideal L2 self and school grades in English (r = .24), a correlation that is barely higher than the correlation between the English ideal L2 self and Mandarin grades (r = .17).…”
Section: Achievement In L2 Motivation Researchmentioning
confidence: 93%
“…In line with the above findings, MacIntyre and Serroul (2015) found "no evidence" (p. 126) that the ideal L2 self is associated with idiodynamic ratings. In at least one study (Moskovsky et al, 2016), the ideal L2 self was a negative predictor of language achievement. Moskovsky et al expressed their surprise that their results "suggest the unusual conclusion that learners with low ideal selves, low [positive L2 learning experience], and low [intended learning effort] are likely to achieve higher scores on L2 proficiency tasks" (p. 649; for further critiques of the ideal L2 self, see Gardner, 2010;Henry & Cliffordson, 2015;Hessel, 2015;Lanvers, 2016;Motha & Lin, 2014;Taylor, 2013, pp.…”
Section: Achievement In L2 Motivation Researchmentioning
confidence: 94%
See 1 more Smart Citation
“…With regard to language motivation research in Saudi Arabia, a few studies have applied Dörnyei's (2005) concept of L2 Motivational Self System theory. For example, a study by Moskovsky et al (2016) identified the components of EFL learning motivation (i.e. ideal L2 self, ought-to-self and L2 learner's experience) in relation to learners' intended ef- 2) What language learning orientations underlie the participants' choice of certain foreign languages?…”
Section: Theories Of Language Learning Motivationmentioning
confidence: 99%